Impacto de las Tecnologías de la Información en las Empresas Latinoamericanas Tras la Pandemia de COVID-19. (2024)
The COVID-19 pandemic drove the adoption of information technologies (IT) in companies around the world, including those in Latin America. This article examines how companies in Latin America have incorporated IT to face the challenges imposed by the pandemic, improving their efficiency, resilience and competitiveness. Through a systematic review of the literature and a bibliometric analysis, the most used IT tools and their impact on different sectors are identified